The Effect of Green Bean Extract on the Nutritional Status of Toddlers - Puspitasari, Nisa Herlina; Kulsum, Ummi; Andriani K, Diah (Advances in Healthcare Research, 2025)
Purpose: This study aimed to determine the effect of green bean (Vigna radiata) juice administration on the nutritional status of malnourished toddlers in Mejobo Village, Kudus District. The hypothesis proposed that daily supplementation of green bean juice would significantly improve nutritional status as measured by Z-scores. Research Method: A pre-experimental design with a total sampling technique was applied to 32 toddlers aged 2–4 years with malnutrition (Z-score: -3 SD to < -2 SD). Respondents were divided into two groups: experimental and control. The intervention consisted of administering 250 ml of green bean juice daily for seven consecutive days. Data were collected through anthropometric measurements before and after the intervention and analyzed using the Shapiro-Wilk test, paired sample t-test, and independent sample t-test. Results and Discussion: The mean Z-score improved from -2.431 pre-intervention to -1.77 post-intervention in the experimental group (p = 0.000), while no improvement occurred in the control group. Independent t-test results showed a significant post-test difference between groups (p = 0.000), confirming the positive effect of green bean juice on nutritional status. Implications: Green bean juice, as a locally sourced supplementary food, is effective for short-term nutritional improvement in malnourished toddlers and can be integrated into community-based nutrition programs. Further studies with longer durations and larger sample sizes are recommended.